Effects of herbicides, hydrogen peroxide and phytohormones on Ganoderma infection in oil palm (Elaeis guineensis Jacq.) roots - Mohan, Durgadevi (2018)
Basal Stem Rot (BSR) caused by Ganoderma is the major disease that infects oil palms (Elaeis guineensis Jacq.). Application of herbicides in plantations for weed control might affect BSR development. The effects of hydrogen peroxide (H2O2) and phytohormones which are key signalling agents in plant defense mechanisms on Ganoderma infection are unknown. Therefore, the objectives of this study are to investigate the effects of herbicides, H2O2 and phytohormones on Ganoderma infection in oil palm roots, and to profile the gene expression of transcripts related to hydrogen peroxide production, hormone biosynthesis and signaling during Ganoderma infection in oil palm roots. The effects of three commonly used herbicides in plantations on the growth of Ganoderma spp. and infection progress in G. boninense PER71-inoculated oil palm seedlings were examined. Evaluation on the tolerance of G. boninense (pathogenic), G. miniatocinctum (pathogenic), and G. lucidum (non-pathogenic) to herbicides revealed that glyphosate (Roundup®, GLY) 1800 ppm-2700 ppm can reduce the growth of all three Ganoderma species. Both Basta (GLA at 750-3000 ppm) and Paraquat (PQ at 325-300 ppm) inhibited the growth of all three Ganoderma species studied except for G. lucidum which was able to grow at 650 ppm PQ. GLA and PQ increased the disease severity of oil palm to Ganoderma infection. The fungus may avoid the herbicide contaminated soil environment and then infected the oil palm seedlings that could have been weakened by the herbicides. The open reading frame and conserved functional domains of eight cDNAs encoding H2O2, phytohormone biosynthesis and signalling in oil palm were analyzed. The transcript abundance of EgRBOHB2 in G. boninense-treated oil palm roots increased 2.42 fold at 3 wpi compared to uninoculated oil palm seedlings. Meanwhile, EgRBOHB1, EgRBOHH and EgHIR did not show significant changes in expression at all three time points. The transcript abundance of EgCOI (jasmonic acid, JA-related) increased at 6 and 12 wpi whereas the transcript abundance EgNPR1 (salicyclic acid, SA-related) increased at 3 wpi, reduced at 6 and 12 wpi; suggesting a well-coordinated signal crosstalk between JA and SA. The expression of EgOPR which is related to JA biosynthesis was up-regulated at 6 wpi; coincided with the upregulation of EgCOI (which perceives JA). The EgACO1 (ethylene, ET- related) was also upregulated at the early stage of infection by 3.2 and 2.2 fold at 3 and 6 wpi in the inoculated oil palm seedlings, respectively. The exogenous application of phytohormones did not suppress the BSR in Ganoderma-inoculated oil palm seedlings while the application of their inhibitors, caused an early onset and more severe disease symptoms. DPI pre-treatment was the only treatment that delayed the onset and reduced the severity of disease symptoms. The distilled water-treated Ganoderma inoculated oil palm fresh root samples (control) had a significantly higher H2O2 level at 3 wpi compared with uninoculated oil palm root samples. However, there was no significant difference in H2O2 level between the Ganoderma inoculated and uninoculated oil palm root sample of the other phytohormone-treated or their inhibitor treated oil palm seedlings. The JA-treated and Ganoderma-inoculated oil palm root sample had the lowest H2O2 level among all the other roots samples at 6 wpi while the SA-treated, Ganoderma inoculated oil palm roots had the lowest H2O2 level among all the other root samples at 12 wpi. The H2O2 inhibitor- treated oil palm roots generally had lower H2O2 level when compared with other treatments. Overall, the H2O2 levels did not correspond to the disease symptoms and severity but showed an increase at the onset of disease symptoms. In conclusion, the findings from this study have given an insight on the effects of herbicides, H2O2, phytohormones and their inhibitors on Ganoderma infection and disease progress of BSR in oil palm seedlings.